The role of surgery on the primary tumor site in bladder cancer with distant metastasis: significance of histology type and metastatic pattern. (27th October 2020) - Wang, Ping; Zang, Shuang; Li, Guangqi; Qu, Weiling; Li, Shuyao; Qiao, Qiao; Jiang, Yuanjun
Abstract: Due to the limited data and research on bladder cancer with distant metastasis, the role of surgery on the primary tumor site in metastatic bladder cancer has been controversial. The aim of this study was to investigate the impact of surgery on patients with metastatic bladder cancer and to identify any factors correlated with the treatment efficacy. Using the Surveillance, Epidemiology and End Results dataset, we performed a large population‐based retrospective study. We classified patents with distant metastasis into subgroups according to their histology type and metastatic pattern. Propensity score matching (PSM) was used to balance clinical variables bias in a 1:3 ratio. A total of 2470 patients with distant metastasis were identified from 2010 to 2016. After PSM, the study eventually included 1068 patients in the surgery group and 356 patients in the non‐surgery group. The histologic types, the number of metastatic sites, liver metastasis, surgery, and chemotherapy were significant prognostic variables for patients with distant metastasis before and after PSM. In terms of histologic types, the survival of patients with transitional cell papillary carcinoma, transitional cell non‐papillary carcinoma and adenocarcinoma can be improved by surgery alone, while the survival of patients with squamous cell carcinoma can be improved only by combining chemotherapy and surgery. In terms of the number of metastatic sites, surgery alone was an independent prognostic factor in patients with 1 or 2 metastatic sites. In terms of the specificity of metastatic organs, surgery affected overall survival for patients with bone metastasis only, liver metastasis only and lung metastasis only, but for distant lymph nodes metastasis only. It may be helpful to classify patients with bladder cancer and distant metastasis into different groups by integrating variables including histology types and metastatic patterns to choose appropriate treatment strategies. Abstract : It may be helpful to classify patients with bladder cancer and distant metastasis into different groups by integrating variables including histology types and metastatic patterns to choose appropriate treatment strategies.